STRATEGI MEMBANGUN KARAKTER ISLAMI MELALUI KEGIATAN PRAMUKA DI MADRASAH TSANAWIYAH ZAINUL IRSYAD PROBOLINGGO - Azizatul Ilmi; M. Jadid Khadavi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to examine the impact of Scout activities on the formation of students' Islamic character at the Zainul Irsyad Madrasah Tsanawiyah (MTs) Probolinggo. Islamic character education is an effort to develop noble morals and spiritual values ​​based on Islamic teachings. This research uses a qualitative approach with data sources from the school principal, scout leaders, teachers and students. The research results show that Scouting as an extracurricular activity is proven to be able to shape students' Islamic character without disrupting learning activities in the classroom. The strategies carried out by Scoutmasters include instilling the moral messages contained in the Dasadharma of Scouting. The Islamic character values ​​developed include: Religious, Responsible, Honest, Independent, Confident, Hard Work, Discipline, Healthy Lifestyle, and Cooperation.